The Pencil Exercise - Juan Cassinelli MD; Philippe Delsol; Clémentine Rieussec MD; Johannes Barth MD (SAGE Publishing, 2024)
Background: Voluntary posterior shoulder instability is a rare condition, with a prevalence of 0.5% to 2.6% in young adults, in which the patient is able to provoke a dislocation or subluxation through voluntary activation of the muscles. Studies have shown results that highlight the importance of abnormal cortical activation in this population and suggest physiotherapeutic treatment as first line. Indications: Currently, there are a wide range of options of physiotherapeutic treatment for this condition, such as muscle reinforcement, scapulohumeral coordination, and/or muscle activation with electrodes, all with acceptable results. Simple, low-cost neuromotor rehabilitation is based on the simplicity of a different approach. We believe that with distal-proximal neuromotor rehabilitation we can improve a physiological muscle function. Technique Description: The goal of the pencil exercise is to stimulate the cerebral cortex by making circular movements with a pen between the fingers, bridging abnormal voluntary stimulation and activation of the shoulder muscles, allowing the patient to focus, by the view, only on hand movements. Results: In this case, we have achieved the bypass of the abnormal voluntary stimulation and activation of the shoulder muscles and improve the patient's physiological shoulder function with the implementation of the pencil exercise. Conclusion: This technique may be an effective option for the treatment of voluntary posterior shoulder dislocation because it is based on the stimulation of the cerebral cortex and not on traditional physiotherapeutic or surgical interventions. It is important to note that more research is needed to validate the results of this technique and determine its long-term efficacy. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.